Assessing yield losses due to iron toxicity in lowland rice under the field conditions - Siriwardana, K.G.D.I; Weerasinghe, W.D.P.; Chandrasekara, K.K.D.; Priyantha, G.D.A.; Rupasinghe, M.G.N.; Wijesinghe, M.R. (My University, 2018)
In Sri Lanka, iron toxicity is recognized as one of the most widespread soil constraints for rice production, particularly in the low country wet zone. This paper investigates plant growth and yield production resulting from iron toxicity in five rice varieties and two advanced breeding lines cultivated on naturally iron-rich soils at the Regional Rice Research and Development Centre, Bombuwala. The experiment was conducted in the 2017/2018 maha season. The randomized complete block design with three replicates was used combing the seven treatments which included three rice varieties and two advanced breeding lines of unknown iron tolerance, and a further two varieties with known tolerant and susceptible traits. The susceptibility/tolerance to iron toxicity was assessed using five endpoints indicating growth and yield production. Significant differences between the seven exposed rice types were noted for all the recorded traits, with some showing superior performances for selected traits. Taking each measured endpoint individually, the lowest leaf bronzing score was recorded in Bw14-820, lowest number of days to 50 % heading in Bw272-6b, highest number of tillers in Bw14-820 and maximum grain yield in Bg366. The tallest plants were recorded in Bw267-3, although for paddy, a ‘moderate height’ is more desirable. Considering a combination of the desirable traits i.e. with regard to all five recorded endpoints, the advanced breeding line Bw14-820 and the variety Bg366 could be taken as showing the highest tolerance to iron toxicity, suggesting that they could be recommended to overcome iron toxicity conditions in lowland areas in the wet zone of Sri Lanka. These varieties could also be further used to develop more tolerant strains of rice in future breeding programmes in the country.
Keywords: Advanced breeding lines, iron toxicity, paddy yields, rice varieties